2020
DOI: 10.1109/ted.2020.3022336
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dark Current Random Telegraph Signals in Silicon and InSb-Based Photodetector Pixel Arrays

Abstract: In this work, the parasitic discrete fluctuation of dark current (dc) called random telegraph signal (RTS) is analyzed in image sensors based on two different semiconductor materials: InSb and silicon. The results show that this dc-RTS phenomenon exhibits similar characteristics on both technologies strongly suggesting a common physical origin. This conclusion is extended to InGaAs and HgCdTe (also referred to as MCT)-based image sensors by comparing the presented results to the existing literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Figure14bcalls also for another comment. Previous studies of radiation induced RTS for Si or InSb reported an exponential amplitude distribution, both before and after irradiation[15] [17]. Here, in Figure14b, distributions appear not perfectly exponential.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Figure14bcalls also for another comment. Previous studies of radiation induced RTS for Si or InSb reported an exponential amplitude distribution, both before and after irradiation[15] [17]. Here, in Figure14b, distributions appear not perfectly exponential.…”
mentioning
confidence: 62%
“…Another well-known radiation induced behavior is the emergence of random telegraph signal (RTS), also called burst or flicker noise. Such an effect has been observed on different material systems [13] such as Silicon transistors or diodes [14], in particular in Si solid-state imagers [15] or even narrower semiconductor materials such as InGaAs [16] and InSb [17]. RTS has also been observed and studied in MCT [18][19] [20].…”
Section: Rts Statistics Evolutionmentioning
confidence: 99%
“…Regarding the exploration from the TIS-1 0 configuration, we conclude that TIS-1 0 is metastable, tending to return to the initial configuration, not consistent with the I 4 migration. This state is however of crucial interest in particular for the understanding of leakage currents observed in microelectronic silicon based-devices 55 whose origin is well identified as coming from the metastability of structural defects, out of the scope of the present study. We therefore do not pursue the exploration of the TIS-1 0 configuration.…”
Section: Diffusion Of Tetra-interstitial Cluster I 4 In Silicon Bulkmentioning
confidence: 99%
“…Up to ten have been measured with the certainty that they do not originate from separate defects. -Observation c [18]: For simple dark currents that do not oscillate, all activation energies above the mid-gap are observed. However, the activation energies of RTS are mainly at midgap.…”
Section: Introductionmentioning
confidence: 96%